Genetic mapping and molecular characterization of the delayed green gene dg in watermelon (Citrullus lanatus) - Gebremeskel, Haileslassie; Umer, Muhammad Jawad; Hongju, Zhu; Li, Bingbing; Shengjie, Zhao; Yuan, Pingli; Xuqiang, Lu; Nan, He; Wenge, Liu (Frontiers in Plant Science, 2023)
Leaf color mutants are common in higher plants that can be used as markers in crop breeding and are important tools in understanding regulatory mechanisms of chlorophyll biosynthesis and chloroplast development. In this study, the delayed green mutant showed a conditional pale green leaf color at the early leaf development but turned to green as the leaf development progressed. Delayed green leaf plants showed reduced pigment content, photosynthetic, chlorophyll fluorescence parameters, and impaired chloroplast development compared with green leaf plants. The delayed green (dg) locus was mapped to 7.48 Mb on chromosome 3 through bulk segregant analysis approach, and the gene controlling delayed green leaf color was narrowed to 53.54 kb between SNP130 and SNP135 markers containing three candidate genes. Sequence alignment of the three genes indicated that there was a single SNP mutation (G/A) in the coding region of ClCG03G010030 in the Houlv parent, which causes an amino acid change from Arginine to Lysine. The ClCG03G010030 gene encoded FtsH extracellular protease protein family is involved in early delayed green leaf development. The expression level of ClCG03G010030 was significantly reduced in delayed green leaf plants than in green leaf plants. These results indicated that the ClCG03G010030 might control watermelon green leaf color and the single SNP variation in ClCG03G010030 may result in early delayed green leaf color development during evolutionary process.